Towards circular production system in the coconut value chain: actor, roles, linkage and constraints in Kilifi County, Kenya - Thuranira Evans Muriuki; Oscar Ingasia Ayuya; Bernard Odhiambo Oloo (Cogent Social Sciences, 2024)
Circular economy has been recognized as an innovation to resolve coconut waste challenges while promoting economic growth. Adoption of circular economy is expected to be a shared responsibility among stakeholders. However, limited research on stakeholder interactions in the coconut value chain hinders the development of collaborative strategies. This study, based on coconut value chain, elucidates stakeholders’ perceptions by identifying key actors, their roles, linkages, level of influence, perceived benefits, and potential constraints faced by actors. Data were collected through a participatory workshop and key informants’ interviews anchored on Social Network Analysis. Twenty-one stakeholders and linkages were identified in the information, product, and finance networks. The National Coconut Development Authority, Kenya Agricultural and Livestock Research Organization, and the Ministry of Agriculture, Livestock, and Fisheries were the most influential stakeholders in the information network. Farmers and cooperatives are centrally positioned in the product network, whereas finance flow is dominated by the Kenya Revenue Authority and the private sector. Despite stakeholders’ positive perceptions, several challenges, such as actors’ limited knowledge and skills impede transition to a circular economy. To enhance adoption of a circular economy, this study recommends formation of more inclusive farmer groups to improve access to information, credit and market linkages.